Transcription factor ThWRKY4 binds to a novel WLS motif and a RAV1A element in addition to the W-box to regulate gene expression. (August 2017) - Xu, Hongyun; Shi, Xinxin; Wang, Zhibo; Gao, Caiqiu; Wang, Chao; Wang, Yucheng
Highlights: In addition to the W-box, ThWRKY4 could specifically bind two other motifs: the RAV1A element and a novel motif WLS. RAV1A and WLS motifs were all present in high numbers in the promoter regions of genes regulated by WRKYs. ThWRKY4 could bind to WLS and RAV1A to regulate gene expression. Five other WRKYs could bind to the RAV1A and WLS motifs. Abstract: WRKY transcription factors play important roles in many biological processes, and mainly bind to the W-box element to regulate gene expression. Previously, we characterized a WRKY gene from Tamarix hispida, ThWRKY4, in response to abiotic stress, and showed that it bound to the W-box motif. However, whether ThWRKY4 could bind to other motifs remains unknown. In this study, we employed a Transcription Factor-Centered Yeast one Hybrid (TF-Centered Y1H) screen to study the motifs recognized by ThWRKY4. In addition to the W-box core cis -element (termed W-box), we identified that ThWRKY4 could bind to two other motifs: the RAV1A element (CAACA) and a novel motif with sequence of GTCTA (W-box like sequence, WLS). The distributions of these motifs were screened in the promoter regions of genes regulated by some WRKYs. The results showed that the W-box, RAV1A, and WLS motifs were all present in high numbers, suggesting that they play key roles in gene expression mediated by WRKYs. Furthermore, five WRKY proteins from different WRKY subfamilies in Arabidopsis thaliana were selected and confirmed to bind to the RAV1A and WLS motifs, indicating that they are recognized commonly by WRKYs. These findings will help to further reveal the functions of WRKY proteins.